Attitude of Russian Youth Towards Suicide - BOGDANOVA, Yulia Zufarovna; ABRAROVA, Zinira Foatovna; KOVROV, Vladimir Fedorovich; HAJRULLINA, Nursafa Gafurovna (Utopía y Praxis Latinoamericana, 2020)
The article presents the results of the interviews carried out with students from a technical university, which showed the relevance of the topics studied, allowing to identify the conditions for the formation of suicidal behavior, its causes and to sketch a portrait of children, adolescents, students and young workers from the position of their vulnerability to suicide, as well as providing measures for the prevention of this type of behavior RESUMEN El artículo presenta los resultados de las entrevistas realizadas a estudiantes de una universidad técnica, que mostraron la relevancia de los temas estudiados, permitiendo identificar las condiciones para la formación del comportamiento suicida, sus causas en general y esbozar un retrato de niños, adolescentes, estudiantes y jóvenes trabajadores desde la posición de su vulnerabilidad al suicidio, así como proporcionar medidas para la prevención de este tipo de comportamiento